Komunikatywność języka prawniczego na przykładzie ustnego ogłoszenia sentencji wyroku = Communicativeness of legal language: A study based on oral pronouncement of the operative part of judgment - Śliwicka, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of the paper is to characterize the features of legal language with regard to its communicativeness by means of analysing one of the common judicial practices, i.e. oral pronouncement of the operative part of judgment. The approach adopted in the study is both semantic and pragmatic in nature.
Keywords: analiza pragmatyczna; analiza semantyczna; deskryptywność; język prawniczy; język prawny; język sądowy; komunikat specjalistyczny; komunikatywność; normatywność; ogłoszenie sentencji wyroku; wyrok; pragmatic analysis; semantic analysis; descriptiveness; legal language; legislative language; court language; communicativeness; specialized message; prescriptiveness; pronouncement of the operative part of judgment; judgments